Hubungan Antara Kualitas Guru dengan Prestasi Belajar Siswa pada Mata Pelajaran Housekeeping - Sri Larasati (Media Wisata, 2014)
Teacher Quality is one factor that determines student achievement, the research to find out the relationship and contribution to the quality of teachers to student achievement in subjects Housekeeping. This Reseach is expected to expective to be useful for teachers to improve performance. To measure student achievement are used Pearson Product Moment analysis method. Of test data analysis can be seen that there is asignificant relationship with the teacher quality anatara student achiement, which toount (7.09423) is greater than ttable (2.021). Whereas the contribution of teacher quality on student achiement is the amount of KP 46.64% while the remaining 53.36% is determinedby other variables is one of the largest employment practices in the industry.